Pengembangan Modul Pembelajaran Online Pada Mata Pelajaran Kimia - Jumi Rahayu; Etin Solihatin; Rusmono - (Jurnal Ilmiah Wahana Pendidikan, 2019)
This study aims at producing an online module, revealing the feasibility of the module, and revealing the effectiveness of the module. The modeling of the research and development was conducted by combining Derek Rowntree model and ILDF (Integrative Learning Design Framework). The stages of Rowntree development model included planning, preparation of writing, writing and re-writing. These stages produced a printed module which was then designed and further developed into an online learning module through ILDF model. The ILDF modeling consists of exploration, enactment and evaluation stages. Based on experts’ judgment in scale 1-4, feasibility tests showed that the developed module is very appropriate to use. In term of learning aspects, this module was scored 3,72 or very good by content experts and 3,68 by learning design experts. As well, its media appropriateness was considered very good by media experts that scored 3,58. The readability of the module is easy, it is proved by 5,05 score of Fog Index. The result of face to face tryout shows that the feasibility score is 3,61. Based on a field trial involving 20 students, the average of pretest is 35,00 and posttest is 78,75. So, the increase of test result in a teaching process using the online module is 43,75. From that result above, it can be concluded that a teaching process in Chemistry using the online module is effective.